A randomized, open-labeled, prospective controlled study to assess the efficacy of frontline empirical intravenous piperacillin/tazobactam monotherapy in comparison with ceftazidime plus amikacin for febrile neutropenia in pediatric oncology patients - Ruchirek Kamonrattana (2020)
© 2019 Asian Pacific Organization for Cancer Prevention. Background: Febrile neutropenia (FN) is the most common complication in pediatric oncology patients. Appropriate empirical antibiotics treatment is essential for treatment outcome. Methods: This study was a randomized prospective controlled study to demonstrate the efficacy of piperacillin/tazobactam (PIP/TZO) monotherapy compared with ceftazidime/amikacin in children with FN. Pediatric oncology patients at Chiang Mai University Hospital, diagnosed with FN, were randomized to receive either PIP/TZO 320 mg/kg/day divided every 8 hours or ceftazidime 100 mg/kg/ day divided every 8 hours plus amikacin 15 mg/kg/day once daily. Treatment responses were compared between the two groups. Results: One-hundred and eighteen febrile neutropenic episodes in 70 patients (42 males and 28 females) were enrolled. The median age was 7 (3-10) years. The early response and complete response to initial treatment were achieved in 48/59 (81.4%) episodes and 41/59 (69.5%) episodes in PIP/TZO group compared with 40/59 (67.8%) episodes and 33/59 (55.9%) episodes in ceftazidime/amikacin group (p-value 0.091 and 0.128, respectively). Treatment modification in PIP/TZO group was required in 18/59 (30.5%) compared with 26/59 (44.1%) patients in ceftazidime/amikacin group (p-value 0.128). Similarly, the duration of fever, duration of neutropenia and duration of antibiotics treatment were not significantly different between two groups. No serious adverse events were observed. Conclusion: The treatment responses of PIP/TZO monotherapy and ceftazidime/amikacin therapy were not significantly different. Both therapies were effective for FN in pediatric oncology patients.